Dogma en kultuur - Koekemoer, J. H. (Hervormde teologiese studies, 1996)
Dogma and culture. The necessity of a critical interpretation of dogma is evident among two lines. First, by its nature dogma is relative to the Word of God. Second, meanings, understanding and relevancies differ from one cultural setting to another. Dogmas should therefore be reinterpreted into new cultural frameworks. One implication of the recognition of cultural relativity is that it enables us to understand the important reason why theology has always been in a position of reformulation. The recognition of cultural relativity means that theologians recognise the need to be more modest, more open to theological discussion and more aware of cultural idolatry.